A model explaining the inability of exciting thermoluminescence (TL) peaks in certain low temperature ranges. (July 2021) - Lawless, J.L.; Chen, R.; Pagonis, V.
Abstract: In some instances reported in the literature, a thermoluminescence peak that was expected to be excited by certain irradiation was not excitable at a certain temperature range below that of the peak although it was excitable at different temperature ranges. Two specific cases of this kind are calcium tungstate and semiconducting diamonds excited by UV light. The resemblance between these two different materials is quite surprising. In both cases, when the sample is UV irradiated at ~80 K and heated up, a glow curve consisting of two peaks is measured, one at ~150 K and the other at ~260 K. However, if the sample is held at temperatures between 150 and 260 K, the efficiency of excitation of the 260 K peak decreases very significantly with temperature so that it can hardly be excited above 200 K. In this work we present a possible energy-level model, previously used to explain the anomalous heating-rate effect, which can account for this rather anomalous effect. The model includes an electron trap, a hole trap and a hole recombination center. The transitions taking place during excitation, relaxation and heating are followed by using the appropriate sets of simultaneous differential equations. Simulation of the process by using a certain set of parameters is reported. Also, a theoretical account with approximations is utilized and both yield practically the same results. The effect of inability of excitation of the second peak at the temperature range between the two peaks is demonstrated. Highlights: Cases of low-temperature ranges at which no TL excitation is possible are studied. Numerical simulations and analytical approximate results are compared. An energy level model with an electron trap, a hole trap and a hole center is used. Very good agreement between simulations and theory. Resemblance of results to experimental effects in CaWO4 and semiconducting diamonds.